Perspectives of Cosmesis following Breast Conservation for Multifocal and Multicentric Breast Cancers - Mona P. Tan; Nadya Y. Sitoh; Yih-Yiow Sitoh (International Journal of Breast Cancer)
Background. Contemporary data suggest that breast conservation treatment (BCT) for multifocal and multicentric breast cancer (MFMCBC) may be appropriate with noninferior local control rates. However, there is a paucity of data to evaluate patient’s satisfaction with cosmetic outcomes after BCT for MFMCBC. This study was performed to bridge this information gap. Methods. All patients treated at the authors’ healthcare facility were included in the study. Patients with MFMCBC who were assessed to be eligible for BCT underwent tumour resection using standard surgical techniques with direct parenchymal closure through a single incision. After at least three years of follow-up, they were invited to participate in a survey regarding their cosmetic outcomes. Results. Of a total of 160 patients, 40 had MFMCBC, of whom 34 (85%) underwent successful BCT. Five-year cancer-specific survival and disease-free survival were 95.7%. Twenty of the 34 patients responded to the survey. No patient rated her cosmetic outcome as “poor.” Analysis indicated low agreement between patients’ self-assessment and clinician-directed evaluation of aesthetic results. Conclusion. BCT for MFMCBC is feasible with acceptable survival and cosmetic outcomes. However, there appears to be a disparity between patient and clinician-directed evaluation of cosmetic results which warrant further research.